Risk and risk factors for epilepsy in shunt-treated children with hydrocephalus. (November 2019) - Schubert-Bast, S.; Berghaus, L.; Filmann, N.; Freiman, T.; Strzelczyk, A.; Kieslich, M.
Abstract: Object: Epilepsy is a major comorbidity in children with hydrocephalus (HC) and has a serious impact on their developmental outcomes. There are variable influencing factors, thus the individual risk for developing epilepsy remains unclear. Our aim was to analyse risk factors for developing epilepsy in children with shunted HC. Methods: A retrospective, single-centre analysis of 361 patients with the diagnosis of HC was performed. Age at HC diagnosis, shunt treatment, development of epilepsy, epilepsy course, and the aetiology of HC were considered. The influence of shunt therapy, including its revisions and complications, on the development of epilepsy was investigated. Results: One-hundred forty-three patients with HC (n = 361) had a diagnosis of epilepsy (39.6%). The median age at the first manifestation of epilepsy was 300 days (range:1–6791; Q1:30, Q3: 1493). The probability of developing epilepsy after HC decreases with increasing age. The most significant influence on the development of epilepsy is that of the HC itself and its underlying aetiology (HR 5.9; 95%-CI [3–10.5]; p < 0.001). Among those, brain haemorrhage is associated with the highest risk for epilepsy (HR 7.9; 95%-CI [4.2–14.7]; p < 0.01), while shunt insertion has a lower influence (HR 1.5; 95%-CI [0.99; 2.38]; p = 0.06). The probability of epilepsy increases stepwise per shunt revision (HR 2.0; p = 0.03 after 3 or more revisions). Five hundred days after the development of HC, 20% of the children had a diagnosis of epilepsy. Shunt implantation at a younger age has no significant influence on the development of epilepsy nor does sex. Conclusion: Children with HC are at high risk for developing epilepsy. The development of epilepsy is correlated mainly with HC's underlying aetiology. The highest risk factor for the development of epilepsy seems to be brain haemorrhage. The age at shunt implantation appears to be unrelated to the development of epilepsy, while structural brain damage at a young age, shunt revisions and complications are independent risk factors. The onset of epilepsy is most likely to take place within the first 500 days after the diagnosis of HC. Highlights: Epilepsy is a frequent co-morbidity in patients with shunt-treated hydrocephalus. The age at shunt implantation seems unrelated to the development of epilepsy. The risk of epilepsy is dependent on the underlying etiology of the HC. There is a multifactorial influence of risk factors on the development of epilepsy in addition to HC. Independent risk factors are: - structural brain damage at a young age - shunt complications - shunt revisions